2023
DOI: 10.1186/s43170-023-00159-1
|View full text |Cite
|
Sign up to set email alerts
|

Cowpea cropping systems, traits preference and production constraints in the upper west region of Ghana: farmers' consultation and implications for breeding

Benjamin Karikari,
Margaret Delle Maale,
Ebenezer Anning
et al.

Abstract: Background Cowpea (Vigna unguiculata (L.) Walp) is used primarily as food for humans and feed for animals. It is also used for soil management within a cropping system. However, cowpea production is confronted with numerous challenges. As such farmers and consumers alike have certain preferences in terms of production and utilization. This present study investigated cowpea cropping systems, traits preference and production constraints among farmers in the Nandom, Lambusie and Lawra districts in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 49 publications
4
0
0
Order By: Relevance
“…According to Tiwari et al (2022) , this includes matching breeding goals to product performance for each segment of end-users or market. The finding from the study that drought tolerance, short cooking times and pest resistance ( Table 2 ) were preferred by both men and women is consistent with that of Karikari et al (2023) . Karikari et al (2023) found that farmers in the Upper West region of Ghana preferred cowpea traits that are drought tolerant, pest resistant and short cooking time.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…According to Tiwari et al (2022) , this includes matching breeding goals to product performance for each segment of end-users or market. The finding from the study that drought tolerance, short cooking times and pest resistance ( Table 2 ) were preferred by both men and women is consistent with that of Karikari et al (2023) . Karikari et al (2023) found that farmers in the Upper West region of Ghana preferred cowpea traits that are drought tolerant, pest resistant and short cooking time.…”
Section: Discussionsupporting
confidence: 76%
“…The finding from the study that drought tolerance, short cooking times and pest resistance ( Table 2 ) were preferred by both men and women is consistent with that of Karikari et al (2023) . Karikari et al (2023) found that farmers in the Upper West region of Ghana preferred cowpea traits that are drought tolerant, pest resistant and short cooking time. The implication is that cowpea farmers are adapting to climate change and variability through the choices they make regarding trait preference.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations